Translating the Ecclesiastes in The 16th century: Giovanni Antonio Fenice's octaves version (TEST Ticontre. Theory Text Translation, 2022)
This paper presents an almost unknown translation in stanzas of the book of Ecclesiastes, prepared in the second half of the 16th century by Giovanni Antonio Fenice. Information on the author, an overview of the text's editions, and some reflections on the translational practice of Fenice are provided.